The Yeoman Jats of Punjab: Time, Expertise and the Colonial Construction of Jat Sikh Identity - Mooney, Nicola (Anthropologica, 2013)
This article explores the social life of colonial exper tise regarding the Jat Sikh community and its intersections with contemporary Jat experiences. While there has been much scholarly attention to Jats as a martial race, here I focus on British iterations of the Jat as yeoman farmer and noble peasant. I argue that British expertise positioned Jats hetero chronically in anterior modern time, even as it contributed to their comparative development, regional dominance and the constructed primordialisms of Jat identity. In closing, I suggest that this particular and privileged position is post colonially discrepant and today mitigates against Jats occupy ing their colonially valorized identities.